Experimental Characterization of Memory Effect, Anomalous Self-Preservation and Ice-Hydrate Competition, during Methane-Hydrates Formation and Dissociation in a Lab-Scale Apparatus - Alberto Maria Gambelli; Federico Rossi (Sustainability, 2022)
This study explores the process of methane hydrate formation and dissociation in a small-scale confined environment and in the presence of a porous sediment. The research is focused on answering the shortage of information about the intrinsic properties of the hydrate formation and dissociation processes, such as memory effect and anomalous self-preservation, in a lab-scale apparatus. Experiments were carried out consecutively and with the same gas–water mixture. The temperature reached during dissociation was high enough to ensure the complete dissolution of water cages. At the same time, it was sufficiently low to keep the system able to retain the memory of the previous formation of hydrates. Different well-known phenomena were observed and described; memory effect, anomalous self-preservation and competition between ice and hydrates were shown in detail. Experiments confirmed that the memory effect improves the process mainly during the initial nucleation phase, while it does not provide significant changes in the following massive growth phase. Finally, experiments proved that the formation process can be divided in two different steps: the initial intense growth, due to the small difference in local equilibrium conditions, and the subsequent asymptotic growth, which continues until the process is completed.